Maritime archaeology and shipwreck ceramics in Malaysia - 374373 Brown, Roxanna M.; Sjostrand, Sten (Kuala Lumpur, Malaysia : Published on the occasion of the exhibition Malaysian Maritime Archaeology by Dept. of Museums & Antiquities in collaboration with Nanhai Marine Archaeology Sdn. Bhd.)
33